Iatrogenic Fistula after Gynecological Operation in a Tertiary level Hospital (Central Medical College Journal, 2023)
Background: Genitourinary fistula constitute a social calamity for the women in the developing countries.The most common cause being obstructed labor, as my study is on fistula due to iatrogenic cause, the most common cause is gynecological surgery. This study has been designed to find out the general information about iatrogenic genitourinary fistula and its outcome.Method: A cross-sectional descriptive study was done on 42 women suffering from urogenital fistula admitted in fistula corner in the department of Obs. & Gynae, Rajshahi Medical College Hospital from March to September 2015. A detailed history was taken to find out the casual factor. All the result had noted in pre-designed history sheet. The data has analyzed by SPSS version II and percentage were calculated.Results: Among 42 of total genitourinary fistula 19 cases of iatrogenic fistula were isolated after proper searching of detailed history. Among the 19 patients 11 (57.90%) patients developed fistula following total abdominal hysterectomy, 4 (21.05%) following laparotomy, 03 (15.79%) following vaginal hysterectomy with anterior colporrhaphy, and 1 (5.26%) patient developed fistula following repair of complete perineal tear. Among 11 patients with total abdominal hysterectomy, 06 were suffering from pelvic inflammatory diseases, 03 patients with fibroid uterus and of the rest 02 patients 01 with endometriosis and 01 patient with dysfunctional uterine bleeding. It was found in majority of the cases (68%) fistula developed within10 days. Among the iatrogenic genitourinary fistulas vesicovaginal type was found to be the most common (84.21%) in this study.Conclusion: The etiology of urogenital fistula is preventable. By utilizing basic principal of surgery, all types of urinary fistula can be repair.Central Medical College Journal Vol 6 No 1 January 2022 Page: 28-33